Analysis of oceanography parameters for the suitability tourism in Bangka Jaya Beach District of Dewantara, North Aceh - Erlangga, Erlangga; Husaen, Yusril; Andika, Yudho; Imamshadiqin, Imamshadiqin; Imanullah, Imanullah (Universitas Malikussaleh, 2022)
Bangka Jaya Beach is located in Krueng Geukueh Village, Dewantara sub-district. Many tourists who often visit Bangka Jaya beach tourism, therefore it is necessary to analyze the suitability of beach tourism, through this research it will be known the level of tourism suitability to the parameters that have been determined as a determination of the level of security for tourists who carry out beach tourism activities. This study aims to determine the condition of oceanographic parameters for the suitability of Bangka Jaya beach tourism in a beach tourism object and analyze the level of tourism suitability based on the potential of existing resources in the coastal area of Bangka Jaya. Primary data that must be taken in the field include tourism suitability data. The tourism suitability data taken include beach type, beach width, water depth, brightness, current speed, water base material, coastal slope, coastal land cover, hazardous biota and freshwater availability. Primary data collection was carried out in the morning when the sea water was high and in the afternoon when the sea water was receding. The sampling method in this study used a purposive sampling method in December - January 2022. The method used was descriptive analysis using the Tourism Suitability Index (IKW) analysis. The results of the study of the tourism suitability index (IKW) obtained the results of measuring the parameters of tourism suitability of 90.47% which was a very suitable category (S1). The tourism suitability parameter in the tourism suitability index table (IKW) can be seen that almost every parameter is included in the very suitable category (S1) of all parameters there are two parameters that fall into the appropriate category (S2), namely the beach type parameter and the beach slope parameter.Keywords: Beach; Oceanography; Suitability; Tour